The Meaning of Wayang Wong Ramayana at Taman Pule Temple, Mas Village As An Inspiration for Painting - Suartana, I Made; Gulendra, I Wayan; Utami, Ni Made Purnami (Program Studi Seni Murni ISI Bali, 2023)
This independent study TA thesis raises the theme of the Meaning of Wayang Wong Ramayana at Taman Pule Mas Village temple as a source of painting creation. Departing from an illustration idea of Wayang Wong Ramayana and the procession carried out by the local community has a very deep meaning both from the Wayang Wong itself and at the time. ritual procession is performed. From this it sparked the author's desire to raise the meaning of Wayang Wong by combining certain techniques and references to achieve the desired meaning. The problem faced is how to visualize the meaning and techniques used in the embodiment of the work so that it looks attractive. The purpose and benefits of this creation are that first, in general, the author wants to embody the meaning of Wayang Wong Ramayana at Taman Pule Mas Village temple into painting, and to be able to embody the meaning or values of Wayang Wong in a symbolic form that reflects the identity of the author.To answer what is the goal in creating this work, the method used by the author in realizing this method is by exploring, improvising, forming, and finalizing the process and combining it with ideas to create 6 works. In realizing the author's work using several references related to techniques from the works of other artists, it is then processed according to the needs of the author to support the meaning to be conveyed and can produce quality work and become the identity of the author.